Vegetable Cultivation with Hydroponic System Nutrient Film Technique In Karang Taruna Gendowang Village - Saufik Luthfianto; M Haidar Aji Pratama; Afrizal Aimudin (Universitas Pancasakti Tegal, 2021)
The result of initial survey in Gendowang Village, Moga District, Pemalang regency is an area with a large potential agricultural area with a total land of 82 ha more and the average population is farming, so it is very potential in developing agricultural systems with hydroponic systems. Enthusiastic citizens are seen at the time of socialization activities. The initial method of applying this technology is an approach to the community, then socialization and workshop. The method used in developing this agricultural system is the application of hydroponic methods with NFT systems. The result is by increasing knowledge and skills in the insertion of this method by 43.95%.